Efficacy of blue-light blocking glasses on actigraphic sleep outcomes: a systematic review and meta-analysis of randomized controlled crossover trials - Luna-Rangel, Francisco A.; Gonzalez-Bedolla, Brenda; Salazar-Ortega, Miranda J.; Torres-Mancilla, Ximena M.; Martinez-Cadena, Salim (Frontiers in Neurology, 2025)
BackgroundEvening exposure to blue light suppresses melatonin, delays circadian phase, and prolongs sleep onset latency, impairing sleep quality. Blue-light blocking glasses (BBGs) are proposed as a non-pharmacological strategy to mitigate these effects, but trial evidence remains inconsistent due to small samples and heterogeneous protocols.ObjectiveTo evaluate the efficacy of BBGs in improving objective sleep outcomes sleep onset latency (SOL), total sleep time (TST), sleep efficiency (SE), and wake after sleep onset (WASO) compared to clear lenses or no intervention in adults.MethodsA systematic search of PubMed, Scopus, and Web of Science identified randomized controlled trials (RCTs) from 2010 to 2024. Eligible studies enrolled adults using BBGs before bedtime and reported actigraphy-derived outcomes. Random-effects meta-analysis was performed using the generic inverse variance method. The review was registered in PROSPERO (CRD420251034611).ResultsThree double-blind crossover RCTs (n = 49) were included. BBGs showed a non-significant reduction in SOL (MD = −4.86 min; 95% CI: −20.23 to 10.52; p = 0.54) and a non-significant increase in TST (MD = 8.75 min; 95% CI: −35.31 to 52.82; p = 0.70). No significant effects were found for SE (MD = −0.61; 95% CI: −7.58 to 6.35; p = 0.86) or WASO (MD = −1.47; 95% CI: −14.94 to 11.99; p = 0.83). Heterogeneity was low (I2 = 0%).ConclusionBBGs may provide small improvements in sleep, but current evidence from RCTs does not support significant effects. Larger, well-powered trials with standardized protocols are needed.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251034611.